Antibiogram Analysis and Altering Antimicrobial Susceptibility Pattern of Multidrug Resistant Pathogens (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: antibiogram; surveillance; changing trends; MDR pathogens